Pengaruh Strategi Integrated Marketing Communication (IMC) terhadap Keputusan Membeli Konsumen pada Bisnis Tour & Travel di Wilayah Daerah Istimewa Yogyakarta - Fransisca Diwati; Tito Imam Santoso (EBBANK, 2015)
This study aimed to examine the effect of Integrated Marketing Communication (IMC) in the variables of motivation, perceptions, and attitudes toward consumer's decision to buy the product tour and travel business in Yogyakarta. Research carried out by multiple regression analysis using primary data in the form of questionnaires. The regression results after testing the validity and reliability of all the explanatory variables showed significant positive effect on the dependent variable. These results indicate that Integrated Marketing Communication (IMC) have an influence on consumer purchase decisions on products Tour and Travel in Yogyakarta.